Tasawuf Kontroversial Prinsip-Prinsip Ajaran Syaikh Mansur Al-Hallaj Dan Penjelasan Tentang Ajarannnya - Budi Handoyo (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2021)
Al-Hallaj's expression which says "Ana al-Haq" (I am the Truth) is interpreted by scholars as something that is very far from the lines of monotheism. The negative view of the fiqh scholars towards the misguided thought of Al-Hallaj is not appropriate, because of their lack of understanding of the nature of Sufism, especially the problem of dzuq and wijdan. The concepts of Hulul, Nur Muhammad and Wihdatul Adyan are the philosophical concepts of al-Hallaj which are the result of his contemplation of science and the circumstances of the surrounding community which are considered too holding onto things beyond the essence of human obligations as servants of God. Most fiqhi groups disbelieve in it, arguing that it is said that humans are united with God. However, there are also many scholars who accept it and defend the thoughts of Al-Hallaj. Imam Al-Hallaj's words are the basis of Dzuq and are in a state of being sick or drunk with God's love.